Taxonomic notes on genus Coelotrypes Bezzi (Diptera: Tephritidae: Trypetinae) with description of two new species - David, K. J.; Hancock, D. L. (Zootaxa, 2019)
Two new species of Coelotrypes Bezzi, C. meremmiae sp. n. and C. paralatilimbatus sp. n. are described from India. Postabdominal structures and the third instar larva of C. luteifasciatus (Senior-White) are also illustrated and described. A key to Oriental species of Coelotrypes is provided.